BICO DO PAPAGAIO: TERRITÓRIO E DESENVOLVIMENTO REGIONAL (1930- 1990) / BICO DO PAPAGAIO: TERRITORY AND REGIONAL DEVELOPMENT (1930-1990) - Miranda, Gilcifran Andrade; Santos, Moacir José dos; Carniello, Monica Franchi (Informe GEPEC, 2023)
O objetivo deste artigo é compreender como o processo histórico de ocupação do território da microrregião Bico do Papagaio, no Estado do Tocantins, entre 1930 e 1990, delineou o seu desenvolvimento. Para alcançá-lo, foram analisados os indicadores econômicos e sociais dos municípios que compõem a microrregião, bem como a identificação e análise dos planos de desenvolvimento federais e estaduais que incidiram sobre a região. Os resultados demonstram que o processo de ocupação do território baseou-se na concentração fundiária e no modelo produtivo da pecuária bovina de corte, fatores determinantes para explicar as assimetrias sociais e econômicas presentes na microrregião. Todos os municípios apresentaram IDH abaixo da média nacional, além de baixo PIB per capita, o que impacta na qualidade de vida da população. Conclui-se que a microrregião apresenta limitações quanto ao se desenvolvimento em decorrência da efetivação de um modelo econômico e social produtor e reprodutor de assimetrias sociais. ABSTRACT : The objective of this paper is to understand how the historical process of occupation of the territory of the Bico do Papagaio microregion, in the State of Tocantins, between 1930 and 1990, outlined its development. To achieve this, the economic and social indicators of the municipalities that make up the micro-region were analyzed, as well as the identification and analysis of the federal and state development plans that affected the region. The results demonstrate that the process of occupation of the territory was based on land concentration and on the productive model of beef cattle raising, determining factors to explain the social and economic asymmetries present in the micro-region. All municipalities had HDI below the national average, in addition to low GDP per capita, which impacts on the quality of life of the population. It is concluded that the micro-region has limitations in terms of development due to the implementation of an economic and social model that produces and reproduces social asymmetries.